The Market in Chinese Social Policy
XI, 169 p.
Keywords: The introduction of market reforms has radically transformed China. Marketizing Social Policy in China examines the impact of a shift to market principles in the critical sector of social policy. The authors demonstrate how social policy reform has been driven by economic transformation, as profound structural change produced inevitable knock-on effects in people's livelihood. Marketization in social policy in turn creates new needs and raises issues that challenge commonly accepted notions of public-private responsibilities in a society undergoing rapid and deep social change.